Can dark matter be a scalar field? - Jesus, J. F. [UNESP]; Pereira, S. H. [UNESP]; Malatrasi, J. L. G. [UNESP]; Andrade-Oliveira, F. (Iop Publishing Ltd, 2016)
In this paper we study a real scalar field as a possible candidate to explain the dark matter in the universe. In the context of a free scalar field with quadratic potential, we have used Union 2.1 SN Ia observational data jointly with a Planck prior over the (lark matter density parameter to set a lower limit on the dark matter mass as m >= 0.12H(0)(-1) eV (c = h = 1). For the recent; value of the Hubble constant indicated by the Hubble Space Telescope, namely H-0 = 73 +/- 1.8 km s(-1) Mpc(-1), this leads to m >= 1.56 x 10(-33) eV at 99.7% c.l. Such value is much smaller than m previously estimated for some models. Nevertheless, it is still in agreement with them once we have not found evidences for a upper limit on the scalar field dark matter mass from SN Ia analysis. In practice, it confirms free real scalar field as a viable candidate for dark matter in agreement with previous studies in the context of density perturbations, which include scalar field self interaction.
Keywords: dark matter theory; supernova type Ia - standard candles; dark matter experiments